De-industrialization: a case study of Dundee, 1951–2001, and its broad implications. Issue 1 (2nd January 2022) - Tomlinson, Jim; Phillips, Jim; Wright, Valerie
Abstract: Using a case study of one Scottish city, Dundee, this article addresses some of the tensions involved in the use of the concept of 'de-industrialization'. Widely used to try to understand economic and social change in the post-war years, this term is complex and controversial. This article unravels some of this complexity, arguing that the term is potentially very helpful, but needs careful definition, nuanced application and recognition of its limits. The focus here is on the impact of changing industrial structures on the labour market. After analysing the processes of firm births and deaths, the study looks at the decline of the 'old staple' industry, jute manufacturing in Dundee. The next sections assess the role of multinational enterprises in re-shaping the employment structure of the city, before looking at the contraction of some of the city's other industries. Attention then turns to the impact of all these changes on the economic welfare of the city. The final section draws conclusions about our general understanding of de-industrialization from the Dundee case.